(untitled) (Journal of Imam Al-Kadhim College, 2023)
Homosexuality is a deviant social problem that has become one of the most common deviations, and the most controversial and expanding, and opinions about it have become conflicting. Some consider it a sin and a chaotic situation directed against Islam. He believes that it is a test that a person is born with and is equipped with. The third opinion believes that it is a natural tendency and is not supposed to be dealt with as a problem or a phenomenon. The current research aims to build a measure of university students’ attitudes towards homosexuality and to identify statistically significant individual differences in attitudes towards homosexuality according to the gender variable (male - female) on a sample of university students consisting of (300) male and female students. The researcher used a set of methods Statistics, including the t-test (T, test) for two independent samples, the discrimination coefficient to extract the discriminatory power, the t-test for one independent sample, Pearson’s correlation coefficient, and the statistical bag program (spss) for data analysis. After the statistical application, the researcher came out with a number of results, recommendations and proposals.